THE IMPORTANCE OF ORGANIZING TEXTILE INDUSTRY ENTERPRISES ON THE BASIS OF A DIGITAL PLATFORM (World Economics and Finance Bulletin, 2023)
This article analyzes the efficiency of textile industry enterprises in the context of digitization. The positive and negative situations affecting the production efficiency of digitalization of enterprise activities are described.production efficiency of digitalization of enterprise activities are described.
Keywords: Textile industry; digital innovations; digital economy